The Role of Psychosocial and Cultural Factors in Adolescent Reproductive Health Literacy in Sinjai Regency - Andi Nurzakiah Amin; Ismi Sultan (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Adolescent reproductive health literacy in Indonesia remains a critical issue, particularly in rural areas such as Sinjai Regency, South Sulawesi. Despite national programs like Pusat Informasi dan Konseling Remaja (PIK-R), gaps persist in integrating psychosocial and cultural dimensions into health education. This study aims to analyze the role of psychosocial and cultural factors in shaping adolescent reproductive health literacy, using an interdisciplinary approach that combines public health, psychology, and socio-cultural analysis. A qualitative descriptive design with a case study approach was employed between September and December 2025. Data were collected from 60 respondents (40 adolescents, 10 parents, and 10 health workers) through semi-structured interviews, focus group discussions (FGDs), and direct observation at schools and Posyandu remaja. Thematic analysis was used to identify recurring patterns, supported by triangulation to ensure validity. The findings reveal three dominant themes: psychosocial readiness, socio-cultural norms, and community-based interventions. Psychosocial factors such as confidence, emotional openness, and peer influence determined adolescents’ willingness to engage in reproductive health education. Socio-cultural norms, including religious values and family expectations, acted as both enablers and constraints, while community leaders served as cultural gatekeepers. Community-based interventions, particularly those involving peers, families, and respected leaders, were found to legitimize and sustain adolescent participation. In conclusion, adolescent reproductive health literacy in Sinjai is shaped by the interaction of psychosocial readiness and socio-cultural acceptance, legitimized through community-based interventions. Effective strategies must therefore integrate psychosocial empowerment, cultural sensitivity, and community participation to enhance knowledge, reduce stigma, and ensure sustainability in health promotion efforts.